Water Quality Characteristics of Sembrong Dam Reservoir, Johor, Malaysia. Issue 1 (July 2016) - Mohd-Asharuddin, S; Zayadi, N; Rasit, W; Othman, N
Abstract: A study of water quality and heavy metal content in Sembrong Dam water was conducted from April - August 2015. A total of 12 water quality parameters and 6 heavy metals were measured and classified based on the Interim National Water Quality Standard of Malaysia (INWQS). The measured and analyzed parameter variables were divided into three main categories which include physical, chemical and heavy metal contents. Physical and chemical parameter variables were temperature, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solid (TSS), turbidity, pH, nitrate, phosphate, ammonium, conductivity and salinity. The heavy metals measured were copper (Cu), lead (Pb), aluminium (Al), chromium (Cr), ferum (Fe) and zinc (Zn). According to INWQS, the water salinity, conductivity, BOD, TSS and nitrate level fall under Class I, while the Ph, DO and turbidity lie under Class IIA. Furthermore, values of COD and ammonium were classified under Class III. The result also indicates that the Sembrong Dam water are not polluted with heavy metals since all heavy metal readings recorded were falls far below Class I.